(untitled) (Research, Society and Development, 2025)
Self-inflicted violence is a global collective health issue, which is constantly driven by the development of mental disorders and socioeconomic, cultural and interpersonal issues that affect the population. This study aims to investigate the influence of the COVID-19 pandemic on notifications of self-inflicted violence in Brazil and characterize an epidemiological profile using sociodemographic data and other variables, to identify variations in epidemiological profiles and potential underreporting during the pandemic period. Thus, notifications were lifted in the period from 2018 to 2024. The data were analyzed qualitatively, generating an epidemiological and statistical profile, through the Poisson regression test and the negative binomial model. The epidemiological profile characterized points to a predominance of female, white, aged 20 to 29 years and adult life cycle, with complete high school. In addition, self-violence occurred predominantly in one’s own home and through poisoning. The results showed a significant increase in notifications of self-inflicted violence in individuals of the mixed-race (“Pardo”), with complete high school education and who already perform this series of behaviors repeatedly. Data filled in as ignored or left blank in the variable race, 5th to 8th grade of elementary school, 15 to 19 years, life cycle (adolescence), and violence considered as non-repetitive or ignored showed a decrease compared to previous years. Thus, it was possible to evidence changes in epidemiological data in the pandemic period, reflecting possible underreporting of self-inflicted violence, evidencing the need for improvements in the notification system, aiming at the availability of real data.